Structural response and damage evaluation of a typical highrise RC building in Dubai under an earthquake with single and multiple peaks - Mahmoud, Sayed; Saleem, Muhammad; Hasanain, Amal; El-Sokkary, H.; Elsharawy, Mohamed; Genidy, Magdy; Abd-Elhamed, Ayman (Journal of Civil Engineering and Management, 2022)
Seismic design codes predominantly assume that earthquakes involve a single ground shaking event; however, earthquakes can occur as a series of shocks. Consequently, the capacity of structures to resist earthquakes with multiple peaks without suffering severe damage is a crucial parameter. This research study evaluates the seismic performance of a high-rise building in Dubai using existing records of single and multiple peaks. Three-dimensional building model was developed considering the actual cross-sections of the horizontal and vertical elements fitting the seismic zone through dynamic response spectrum analysis. The building is analyzed using the nonlinear regime employing fast-nonlinear timehistory analysis with the scaled NS and EW records of the Niigata earthquake. The main finding of this work is that records with multiple peaks significantly increase structural response and magnify the structural damage compared with records of single-peak earthquakes; thus, earthquakes involving multiple shocks significantly increase the risk of structural failure in a building.